Surgical Management of Patellofemoral Instability in Adolescents with High Grade Trochlear Dysplasia. Issue 5 (31st May 2022) - Wilson, Benjamin R.; Nunally, Kianna D.; Cook, Danielle L.; Hussain, Zaamin B.; Zheng, Evan T.; Yen, Yi-Meng; Kramer, Dennis E.; Micheli, Lyle J.; Kocher, Mininder S.; Heyworth, Benton E.
Background: High-grade trochlear dysplasia (HGTD) has previously been identified as a risk factor for failure of surgical management of patellofemoral instability (PFI). However, limited data exists on the influence of the type of surgical procedure performed on postoperative outcomes in these patients. Hypothesis/Purpose: The purpose of this study was to identify the rates of failure of primary PFI surgery in patients with HGTD compared to those without HGTD and to assess the effect of the type of surgery on recurrent instability and return to OR. Methods: A retrospective review was performed on patients aged ≤19 years who underwent primary surgery for PFI at a single tertiary care center between 2008 and 2017. Patients underwent procedures including medial retinacular plication/reefing/advancement (MRP), graft-based medial patellofemoral ligament reconstruction (MPFLR), tibial tubercle osteotomy with or without MRP (TTO), or combined MPFLR + TTO. Exclusion criteria were BMI >30kg/m 2, surgery for fixation of chondral fractures >1cm, and diagnosis of a syndromic disorder. Trochlear dysplasia was evaluated based on pre-operative MRI according to the Dejour classification system. Those with Dejour grade B or higher were designated as having HGTD. Comparisons were made between HGTD patients and non-HGTD patients, with logistic regression utilized to determine if surgery type was associated with recurrent PFI and revision PFI surgery. Results: 303 patients (mean age 15.1 years, 71% female) underwent primary surgical stabilization for PFI with median follow up time of 3.0 years. Approximately half (149/303, 49%) of the cohort had HGTD. Demographics were comparable between HGTD and non-HGTD patients (Table 1). HGTD and non-HGTD cohorts showed similar rates of post-operative instability, revision PFI surgery, and non-PFI secondary surgery. HGTD patients (Table 2) who underwent MPFLR had a 63% decrease in the odds of post-operative PFI compared to those who underwent MRP (OR=0.37; p=0.03). HGTD patients who underwent TTO had an 80% decrease in the odds of post-operative PFI compared to patients undergoing MRP (OR=0.20; p=0.002). Conclusion: Adolescents with PFI and HGTD have similar results after surgical stabilization to those patients without HGTD. Within the HGTD cohort, however, the type of surgery performed significantly influenced outcome. Patients with HGTD that underwent MRP had significantly more recurrent PFI and revision PFI surgery than patients that underwent other procedures, suggesting a limited role for this procedure in this sub-population of PFI patients. Table 1. Patient Demographics and Outcomes Compared Between Trochlear Dysplasia Groups (n=303). Table 2. Outcomes of Patients with HGTD Compared by Type of Surgery (N=149).